Answer:
f(x) = 2x – 3
f(0) = 2(0) – 3 = -3
f(1) = 2(1) – 3 = 2 – 3 = -1
(f(0) + f(1))/2 = (-3 - 1)/2 = -4/2 (f(0) + f(1))/2 = - 2
10.3 = 0.6y...divide both sides by 0.6
10.3 / 0.6 = y
17.17 = y <=
Answer:
K = 3/2
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
k−9=5(k−3)
k+−9=(5)(k)+(5)(−3)(Distribute)
k+−9=5k+−15
k−9=5k−15
Step 2: Subtract 5k from both sides.
k−9−5k=5k−15−5k
−4k−9=−15
Step 3: Add 9 to both sides.
−4k−9+9=−15+9
−4k=−6
Step 4: Divide both sides by -4.
-4k/-4 = -6/-4
K = 3/2
Answer: 24
Step-by-step explanation:
Answer:
14.2857% decrease
≈ 14.3% decrease
Step-by-step explanation:
nearest tenths : 14.3%
nearest hundredths : 14.29%
nearest thousandths : 14.286%
I hope my answer is correct, I provided more options because I wasn't sure what nearest percent wanted.
Hope this helps!